The Vertical Distribution of Helopeltis bradyi and Oxyopes javanus on Tea - Novira Maya Sari; Arman Wijonarko; Fransiscus Xaverius Wagiman (Jurnal Perlindungan Tanaman Indonesia, 2019)
Helopeltis bradyi is the main pest of tea plants. Ecological characteristics of this pest are important to be understood to support the development of their management and control measures. This study aimed to determine the coexistence and vertical distribution pattern of H. bradyi and its predator, Oxyopes javanus, on tea plant parts. The study was conducted at the PT Pagilaran tea plantation in Central Java, in the 2018 rainy season. Population observations were carried out in situ on 20 infested sample-trees taken randomly, for 10 consecutive days, in the morning, at noon, and in the afternoon. Vertical distribution patterns were determined based on Poisson dispersion index (DI), negative binomial, and Green index (GI). The results showed that the O. javanus spider was found preying on H. bradyi. Coexistence between this pest and predator in the same part of the plant, the pest, and the predator, occurred in the morning were 50.0, 42.8, and 7.2%; at noon were 58.3, 41.7, and 0%; and at the afternoon were 66.7, 33.3, and 0%, respectively. The parts of the plant for the coexistence are pekoe leaves; the 1st, 2nd, 3rd, and 4th of young leaves; and 1st of older leaves. The pattern of vertical distribution in the morning, at noon and in the afternoon for H. bradyi was the weak clump, while for O. javanus was uniform. The ratio of predator: prey in the morning, at noon and in the afternoon was 1:10.7, 1:16.7, and 1:10.0, respectively.